Respostas

  • Usuário do Brainly
2014-08-31T01:05:04-03:00
Olá, Kelvin !

\dfrac{3}{4x^3y}+\dfrac{2}{3x^3y}-\dfrac{1}{6x^3y}

Veja que, \text{mmc}(4,3,6)=12, logo:

\dfrac{3}{4x^3y}+\dfrac{2}{3x^2y}-\dfrac{1}{6x^3y}=\dfrac{9+8-2}{12x^3y}=\dfrac{15}{4x^3y}.

Seja Q(x) o monômio em questão. Temos:

Q(x)=\dfrac{\dfrac{15}{4x^3y}}{\dfrac{3}{2x}}~~\Rightarrow~~Q(x)=\dfrac{15}{4x^3y}\cdot\dfrac{2x}{3}~~\Rightarrow~~Q(x)=\dfrac{30x}{12x^3y}

\boxed{Q(x)=\dfrac{5}{2x^2y}}

Se x=-2 e y=6, temos:

Q(x)=\dfrac{5}{2\cdot(-2)^2\cdot6}=\dfrac{5}{2\cdot4\cdot6}=\dfrac{5}{48}.
1 5 1
O resultado era pra dar 45 não 48